Sustainable Rice Husk Mixture Fibre–Stripe Polyethylene Film Composites: Effects of Recycling and Alkali Treatment on Water Absorption, Flammability, Density, and Mechanical Properties - Mathias Bifam; Yakubu Joshua; Alheri Andrew; Peter Micheal Dass (Darul Yasin Al Sys, 2026)
The increasing accumulation of plastic and agricultural waste has intensified interest in sustainable polymer composites that combine improved material performance with environmental value. This study investigates the water absorption, flammability, density, hardness, and tensile strength of composites prepared from used and unused stripe polyethylene (PE) films and rice husk mixture fibres, with and without NaOH treatment. Water absorption testing showed that composites made with used PE exhibited the highest uptake, reaching 88.35% after 24 hours, which was attributed to polymer degradation and microvoid formation, whereas unused PE composites demonstrated superior moisture resistance, with absorption as low as 2.19%. NaOH-treated rice husk improved fibre–matrix adhesion and produced intermediate absorption values. Flammability analysis revealed that used PE composites burned faster, with rates of 0.88–0.39 mm/sec, compared with unused PE composites, which recorded 0.65–0.28 mm/sec, while NaOH treatment reduced flammability through enhanced char formation and silica content. Density measurements indicated lower values for used PE composites, ranging from 1.18 to 2.25 g/cm³, due to chain scission and void formation, whereas unused PE composites maintained higher densities of up to 2.75 g/cm³. Hardness and tensile strength increased with PE content, with unused PE composites achieving the highest values of 36.60 MPa and 54.90 MPa, respectively, while NaOH-treated rice husk composites provided balanced mechanical reinforcement. The study concludes that unused PE offers superior mechanical performance and moisture resistance, whereas NaOH-treated rice husk enhances interfacial bonding and fire-safety characteristics. These findings contribute to the development of sustainable rice husk–polyethylene composites as potential eco-friendly materials for packaging, construction, and automotive applications.